2015
DOI: 10.1007/s00198-015-3110-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum 25(OH)D and bone density and microarchitecture as measured by HR-pQCT

Abstract: These data suggest a weak relationship between serum 25(OH)D and bone microarchitecture in this population of mostly vitamin-D-sufficient participants, and there were no indications of negative effects related to the high supplementation levels. These data provided a basis to design and implement our 3-year dose-dependent randomized controlled trial investigating the effects of vitamin D supplementation on bone health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…However, the link between serum vitamin D and bone microarchitecture has been described as weak. 35 Furthermore, in the study of patients with MACE, 25-hydroxyvitamin D levels were not associated with TBS. 16 Secondly, we were not able to clearly estimate the duration of CS prior to its diagnosis, a parameter that may play a role in the intensity of glucocorticoid-related bone alterations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the link between serum vitamin D and bone microarchitecture has been described as weak. 35 Furthermore, in the study of patients with MACE, 25-hydroxyvitamin D levels were not associated with TBS. 16 Secondly, we were not able to clearly estimate the duration of CS prior to its diagnosis, a parameter that may play a role in the intensity of glucocorticoid-related bone alterations.…”
Section: Discussionmentioning
confidence: 88%
“…Firstly, it is a retrospective study and confounding osteoporotic factors such as, family background of fractures, smoking status and vitamin D levels that were not accurately recorded may have interfered with our results. However, the link between serum vitamin D and bone microarchitecture has been described as weak . Furthermore, in the study of patients with MACE, 25‐hydroxyvitamin D levels were not associated with TBS .…”
Section: Discussionmentioning
confidence: 94%
“…Women with 25(OH)D in the upper quartile did not have significantly lower femoral subtrochanteric cortical porosity than did those in the lowest quartile (42.0% vs. 43.0%), in the current study. One reason for this lack of association could be that we included a relatively young (mean age, 68 years) and healthy cohort of postmenopausal women, with serum 25(OH)D mainly in the normal range, similar to the Boyd et al study [26].…”
Section: (Oh)d and Pth Between 25(oh)d Or Pth And Season Of Blood mentioning
confidence: 99%
“…However, few studies have investigated whether vitamin D is associated with bone turnover markers and cortical porosity. One study reported that low serum 25(OH)D is associated with increased cortical porosity in elderly men (mean age, 80 years) [25], whereas 25(OH)D was not associated with cortical porosity in another study of women and men (mean age, 55 years) [26]. In individuals with primary hyperparathyroidism and very high serum parathyroid hormone (PTH) levels, cortical volumetric bone mineral density (BMD) was reduced due to increased cortical porosity.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, unfortunately, information about environmental factors such as dietary intake, alcohol consumption, exercise, and smoking, were not acquired for all cohorts and is a limitation, as they may affect bone microstructure. (29)(30)(31)(32)(33)(34) Our prior work in premenopausal women suggests that Chinese-American women tend to have more lifestyle risk factors for poorer skeletal health, including lower calcium and vitamin D intake and exercise levels compared with white women; (10) yet despite this, Chinese-Americans have more favorable microstructure. Adjustment for these covariates in our prior study tended to accentuate the more favorable microstructure in Chinese-Americans.…”
Section: Discussionmentioning
confidence: 99%